2018
DOI: 10.1016/j.heliyon.2018.e00562
|View full text |Cite
|
Sign up to set email alerts
|

Combination antibiotics against Pseudomonas aeruginosa, representing common and rare cystic fibrosis strains from different Irish clinics

Abstract: ObjectivesTo evaluate the effect of antibiotic combination therapy versus single therapy against cystic fibrosis strains of Pseudomonas aeruginosa identified as common and rare among patient groups in different Irish hospitals.MethodsThis study compares the susceptibility profiles of P. aeruginosa isolates from different cystic fibrosis (CF) clinics in Ireland, collected from 2004–2005. Strains were recovered in small numbers and typed by pulsed-field gel electrophoresis. Five common clonal variants were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…At the highest concentration of the metal-tdda-phen complexes (64 µg/mL) in combination with gentamicin (32 µg/mL), there was >90% biofilm removal for CF2 and CF3 and >83% for CF1, and the fractional inhibitory concentration (FIC) index showed a positive synergism for all three metal-tdda-phen complexes in the presence of gentamicin. A recent clinical study in Ireland on cystic fibrosis P. aeruginosa clinical isolates with the same laboratory reference strains (ATCC 27853 and PAO1) showed that tobramycin (aminoglycoside) and ceftazidime (cephalosporin) was the only effective combination to show positive synergism (FIC ≤ 0.5) against a mature biofilm of a single clinical isolate at a concentration of 64 mg/L [ 41 ]. However, as mentioned earlier, the evolving resistance to antibiotics is problematic and of concern when considering combinations of established antibiotics for the treatment of P. aeruginosa infections in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the highest concentration of the metal-tdda-phen complexes (64 µg/mL) in combination with gentamicin (32 µg/mL), there was >90% biofilm removal for CF2 and CF3 and >83% for CF1, and the fractional inhibitory concentration (FIC) index showed a positive synergism for all three metal-tdda-phen complexes in the presence of gentamicin. A recent clinical study in Ireland on cystic fibrosis P. aeruginosa clinical isolates with the same laboratory reference strains (ATCC 27853 and PAO1) showed that tobramycin (aminoglycoside) and ceftazidime (cephalosporin) was the only effective combination to show positive synergism (FIC ≤ 0.5) against a mature biofilm of a single clinical isolate at a concentration of 64 mg/L [ 41 ]. However, as mentioned earlier, the evolving resistance to antibiotics is problematic and of concern when considering combinations of established antibiotics for the treatment of P. aeruginosa infections in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…3-day grown biofilms used here, showed a significant increase in the concentrations of imipenem (of up to 1000-fold) required to eradicate efficiently (MBEC 2048 µg/mL), and 5 two-fold increase for tobramycin (MBEC 64 µg/mL). These observations are in agreement with literature (Hengzhuang, Wu et al 2011, Kapoor andMurphy 2018), that a 3-day P. aeruginosa biofilm model, can be considered "mature", usually exhibiting MBEC of 100 -1000 fold higher than MBC.…”
Section: Discussionsupporting
confidence: 93%
“…CV staining has been suggested in a number of recent publications to be used as a standard proxy for biofilm susceptibility assays (Haney, Trimble et al 2018, Kapoor and Murphy 2018). It is known that CV stains both live and dead bacterial populations, and all EPS components in varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the antibacterial activity of selected antibiotics was screened and ciprofloxacin was found most effective which was similar to the finding of Kapoor and Murphy. [ 23 ] The methanol extract of clove exhibited higher zone of inhibition against reference strain PA01, clinical isolate 2 and clinical isolate 4. Almost similar activity of clove was reported by Pandey and Singh, Mostafa et al .…”
Section: Discussionmentioning
confidence: 99%